Use of the Peltier effect in the design of cooling systems - Kondratiev, Kyrylo (National Technical University "Kharkiv Polytechnic Institute", 2025)
The primary practical use of the Peltier effect in semiconductors is to generate cold for thermoelectric cooling devices or, conversely, to heat objects at low or negative temperatures—thermostabilization. The thermoelectric cooling method offers a number of advantages compared to other cooling techniques. Thermoelectric devices are characterized by simple control, precise temperature regulation, silent operation, and high reliability. Despite the low cooling capacity, an efficient scheme for applying Peltier elements was developed to cool the lubricant in the sliding bearing systems of rolling mills at metallurgical plants.
Keywords: lubrication systems; thermal regime of lubricant; oil cooling in bearings; thermoelectric effects; Peltier effect; heat exchanger; thermostabilization; Peltier element